The Impact of Digital Media on Religious Education: Opportunities and Challenges - Gerard Wiegers; Anneke Goudswaard; Wouter Hanegraaff (International Forum of Researchers and Lecturers, 2024)
The digital age has introduced new opportunities and challenges for religious education. This article analyzes how digital media platforms and online learning tools have transformed the way religious education is delivered. It highlights the potential benefits, such as wider reach and accessibility, while also addressing challenges related to content quality, misrepresentation, and the need for critical media literacy.